Yohannes II (r. May 10, 1769 – October 15, 1769) - Bekele, Shiferaw (Aethiopica, 2002)
The knowledge of the reign of Yohannes II (r. May 10, 1769–October 15, 1769) is so far based on a brief account in Bruce’s book. This account, however, contains errors (that Yohannes II was poisoned to death). This paper brings to light an Ethiopian document (a brief contemporary chronicle) on the short-lived reign of this man. It is published with a translation and annotation. On the basis of a careful examination of the chronicle and the other fragmentary information we obtain from Salt, we conclude in this paper that firstly Yohannes was not poisoned to death (he rather died a natural death) and secondly the story of the amputation of his arm by Bekfa should at best be treated with caution because there is evidence that throws doubt on its veracity.